2021
DOI: 10.24996/ijs.2021.62.8.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flexible Multi-Walled Carbon Nanotubes Network Sensor to Freon Gas Detection

Abstract: MWCNTs-OH was used to prepare a flexible gas sensor by deposition as a network on a filter cake using the method of filtration from suspension (FFS). The morphological and structural properties of the MWCNTs network were characterized before and after exposure to Freon gas using FTIR spectra and X-ray diffractometer, which confirmed that the characteristics of the sensor did not change after exposure to the gas. The sensor was exposed to a pure Freon134a gas as well as to a mixture of Freon gas and air with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The spectra show a special peak of MWCNTs-OH that appears at the angle of 2𝜃 =26.400 ° which belong to the (002) plane,other peaks are seen to demonstrate a characteristic of the embedded NP S . The spectrum of MWCNTs-OH embedded with (PANI,PPy) NPs shows diffraction peak at angle of (2θ=25.85 00 ˚, 2θ=25.9000 ˚),which belongs to (002) plane shown in table (3).Table (2) represents the values of (2θ) of the peaks and structural parameters of the networks. The particle size and morphology of the pure MWCNTs-OH were studied using the scanning electron microscope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra show a special peak of MWCNTs-OH that appears at the angle of 2𝜃 =26.400 ° which belong to the (002) plane,other peaks are seen to demonstrate a characteristic of the embedded NP S . The spectrum of MWCNTs-OH embedded with (PANI,PPy) NPs shows diffraction peak at angle of (2θ=25.85 00 ˚, 2θ=25.9000 ˚),which belongs to (002) plane shown in table (3).Table (2) represents the values of (2θ) of the peaks and structural parameters of the networks. The particle size and morphology of the pure MWCNTs-OH were studied using the scanning electron microscope.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the sensitivity increases when doped with PANI and PPy NP s . Saleh, prepared MWCNTs-OH was used to a flexible gas sensor by deposition as a network on a filter cake using the method of filtration from suspension (FFS) [3].Gas sensors are usually classified as chemical detectors. It includes a transducer and an active layer, which converts the desired chemical reactions to an electronic signal, for example, resistance change, voltage, current, or frequency [4].…”
mentioning
confidence: 99%
“…Today, many studies focus on preparing films from carbon nanotubes and improving their properties by adding conductive polymers and metal nanoparticles [11][12][13]. Present work involves synthesizing multi-walled carbon nanotubes networks coated with a conductive polymer (PPy) and PPy doped with metallic nanoparticles (Ag and Cu) separately.…”
Section: Introductionmentioning
confidence: 99%